2021
DOI: 10.1186/s13620-021-00193-3
|View full text |Cite
|
Sign up to set email alerts
|

Why do Irish pig farmers use medications? Barriers for effective reduction of antimicrobials in Irish pig production

Abstract: Background In addressing the threat of antimicrobial resistance, it is critical to understand the barriers to the uptake of strategies for the reduction of antimicrobial use (AMU) in the pig industry. In several EU countries, factors such as education level, habits and social pressures are recognised as affecting farmers’ decision-making process in relation to AMU. However, there is a lack of information on the Irish scenario. The aim of this study was to investigate pig farmers’ perspectives a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Reducing the need for AMU is more challenging, however, requiring improvements in overall herd health. Irish farmers previously identified economic concerns over international competition and cost effectiveness of alternatives to AMU as barriers to reducing in-feed medication [40], and there were similar findings amongst British farmers, where high investment costs and staffing difficulties were cited as barriers [30]. Nevertheless, this challenge has been met in other countries [90,91] and can be achieved without impacting performance or profit [92][93][94].…”
Section: Implications For Irish Pig Sectormentioning
confidence: 76%
See 1 more Smart Citation
“…Reducing the need for AMU is more challenging, however, requiring improvements in overall herd health. Irish farmers previously identified economic concerns over international competition and cost effectiveness of alternatives to AMU as barriers to reducing in-feed medication [40], and there were similar findings amongst British farmers, where high investment costs and staffing difficulties were cited as barriers [30]. Nevertheless, this challenge has been met in other countries [90,91] and can be achieved without impacting performance or profit [92][93][94].…”
Section: Implications For Irish Pig Sectormentioning
confidence: 76%
“…Finally, socio-economic and demographic factors such as age, gender, education or years of experience [36] and attitudes to AMR [37] can influence on farm AMU, although their relative importance appears to differ depending on nationality [17]. In general, pig farmers perceive AMs as an effective and cost-efficient tool in disease management [30,[38][39][40] and, at least in the past, were poorly aware or unconcerned about the risks of AMR [38,39,41].…”
Section: Introductionmentioning
confidence: 99%
“…Commercial pig farms account for about 74% of intensive administration of pharmaceutical compounds due to their beneficial effects on growth rate and feed conversion efficiency and for the prevention and treatment of disease, which has thus become a concern and potential risk (Diana et al, 2021 ). Studies have shown the increased presence of veterinary pharmaceuticals in different environmental compartments (Obimakinde et al, 2016 ) where these substances are found either as parent materials or as a range of transformed products in the aquatic environment (Hu & Cheng, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotic efficiency in the young bull sector is decreasing due to the general overuse of antibiotics. This phenomenon is extensive and of growing concern worldwide, with similar problems arising in other countries (Diana et al, 2021; Laxminarayan et al, 2013; OECD, 2015; Sneeringer et al, 2020).…”
mentioning
confidence: 98%